2022
DOI: 10.3390/horticulturae8070624
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharins Used Together with Tebuconazole Enhances Resistance of Kiwifruit against Soft Rot Disease and Improves Its Yield and Quality

Abstract: Botryosphaeria dothidea is one of the most frequent pathogens of soft rot disease in kiwifruit. The aim of this study was to investigate the role of oligosaccharins used together with tebuconazole to control soft rot and their influences on kiwifruit’s disease resistance, growth and quality. The results show that tebuconazole displayed a toxicity against B. dothidea RF-1 with 0.87 mg kg−1 of EC50 value. Oligosaccharins used together with tebuconazole effectively managed soft rot with 84.83% of the field manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In addition, pyraclostrobin is a broad-spectrum and efficient strobilurin fungicide [16][17][18][19][20][21]. Wang et al [35] found that oligochitosan combined with tebuconazole could effectively improve kiwifruit's resistance to soft rot disease. Subsequently, we found that the ability of pyraclostrobin to control powdery mildew in R. roxburghi could be effectively promoted by chitosan [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, pyraclostrobin is a broad-spectrum and efficient strobilurin fungicide [16][17][18][19][20][21]. Wang et al [35] found that oligochitosan combined with tebuconazole could effectively improve kiwifruit's resistance to soft rot disease. Subsequently, we found that the ability of pyraclostrobin to control powdery mildew in R. roxburghi could be effectively promoted by chitosan [21].…”
Section: Discussionmentioning
confidence: 99%
“…Oligochitosan can stimulate the gene expression of disease-resistant substances in plants, including chitinase, glucanase, phytoalexin, and PR protein [30][31][32]. Wang et al [35] found that oligochitosan could notably enhance the resistance substances and enzyme activity of kiwifruit, and Zhang et al [21] reported that pyraclostrobin could partly enhance the phenolics, flavonoids, soluble protein, and SOD activity of R. roxburghii. In this work, oligochitosan combined with pyraclostrobin clearly enhanced the effects of their lone application on the protein, phenol, and flavonoid contents and SOD, POD, PAL, and PPO activities of the leaves; this combination also enhanced the inhibiting effects on the MDA level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the meantime, it easily triggers pathogen resistance with the growth of application frequency [ 23 , 24 ]. Noteworthily, Wang et al [ 25 ] reported that oligosaccharins could be applied as an adjuvant to enhance tebuconazole’s control of soft rot disease of kiwifruit and reduce tebuconazole application. In that way, whether some natural products or biomolecules can be applied as an adjuvant to pyraclostrobin to more effectively control powdery mildew of R .…”
Section: Introductionmentioning
confidence: 99%